SQL on FHIR - Tabular views of FHIR data using FHIRPath - John Grimes; Ryan Brush; Nikolai Rhyzhikov; Piotr Szul; Joshua Mandel; Dan Gottlieb; Grahame Grieve; Bashir Sadjad; Arjun Sanyal (npj Digital Medicine)
Abstract Challenges exist with the adoption of Fast Healthcare Interoperability Resources (FHIR) within analytics, including the difficulty in transforming complex data structures, and performance issues when querying large datasets in their native JSON or XML formats. In 2023, an international working group began work on a solution to this problem that would be easier to implement than existing approaches. Over the course of 18 months, the group authored a new specification and validated it through the development and testing of multiple independent implementations. The outcome of this work is a standard, implementation-agnostic method for defining views that produce tabular data from FHIR resources. SQL on FHIR view definitions can be written to cover common use cases and can be executed across a variety of technology platforms. We evaluate the feasibility of this approach by replicating findings from an existing study across multiple view runner and database implementations, demonstrating portability and consistency.